Analisis Deskripsi Pemilihan Tema Konten untuk Pemasaran Sosial Media Instagram dalam peningkatan personal Branding - Ihsan, Taufik; Fajar Ariwibowo, Muhammad; Mawarindani Indra, Azalia; Triwahyuni, Atin (MDP Student Conference, 2024)
Digital marketing is a marketing activity that utilizes technology and the internet. Digital marketing activities are a common thing carried out by many companies today, and there are various examples of digital marketing such as search engine optimization, affiliate marketing, content marketing, and social media marketing. Digital marketing activities have many benefits for both novice and experienced entrepreneurs. One of the digital marketing methods that is getting a lot of attention in Indonesia is social media marketing. Social media marketing is marketing by optimizing social media as the main media. According to We Are Social [2], social media users in Indonesia have reached 167 million, and the percentage of social media users is 60.4% of all Indonesian society.